2022
DOI: 10.1177/1358863x221122552
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative evaluation and perioperative management of patients undergoing major vascular surgery

Abstract: Patients undergoing major vascular surgery have an increased risk of perioperative major adverse cardiovascular events (MACE). Accordingly, in this population, it is of particular importance to appropriately risk stratify patients’ risk for these complications and optimize risk factors prior to surgical intervention. Comorbidities that portend a higher risk of perioperative MACE include coronary artery disease, heart failure, left-sided valvular heart disease, and significant arrhythmic burden. In this review,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 143 publications
(245 reference statements)
0
12
0
Order By: Relevance
“…Though generally well-tolerated, there are contraindications to exercise stress echocardiography that should be followed to minimize adverse events. Contraindications include patients with active acute coronary syndrome (ACS) <48 h, persistent and poorly controlled ventricular or supraventricular tachyarrhythmias, malignant hypertension, symptomatic severe aortic valve stenosis, acute aortic dissection, severe, symptomatic, poorly controlled heart failure, acute pulmonary embolism, acute pericarditis and/or myocarditis, and severe obstructive left ventricular outflow tract (LVOT) obstruction (3,4,33,34). Importantly, even patients without a resting LVOT obstruction may develop exertional hypotension and/or syncope due to an inducible, latent LVOT obstruction (35).…”
Section: Contraindicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though generally well-tolerated, there are contraindications to exercise stress echocardiography that should be followed to minimize adverse events. Contraindications include patients with active acute coronary syndrome (ACS) <48 h, persistent and poorly controlled ventricular or supraventricular tachyarrhythmias, malignant hypertension, symptomatic severe aortic valve stenosis, acute aortic dissection, severe, symptomatic, poorly controlled heart failure, acute pulmonary embolism, acute pericarditis and/or myocarditis, and severe obstructive left ventricular outflow tract (LVOT) obstruction (3,4,33,34). Importantly, even patients without a resting LVOT obstruction may develop exertional hypotension and/or syncope due to an inducible, latent LVOT obstruction (35).…”
Section: Contraindicationsmentioning
confidence: 99%
“…Stress echocardiography is performed via multiple modalities and includes exercise stress testing, either via a treadmill or upright/supine bicycle, or pharmacologically-mediated testing with the administration of dobutamine or vasodilators (i.e., dipyridamole or adenosine) (3). Both exercise and pharmacologic stress echocardiography have excellent sensitivities and specificities in the diagnosis of obstructive coronary artery disease, with a sensitivity of between 80% and 85% for exercise stress echocardiography and 79%-83% for dobutamine stress echocardiography, along with a specificity between 80% and 88% and 82% to 85%, respectively (3,4). Since the introduction of stress echocardiography, the indications have expanded to not only include an assessment of coronary artery disease, but to also encompass indications such as an assessment of valvular disease (i.e., mitral stenosis, aortic stenosis), congenital heart disease, obstructive hypertrophic cardiomyopathy, diastolic function, and myocardial viability.…”
Section: Introductionmentioning
confidence: 99%
“…Management of this increased cardiovascular risk within surveillance populations does not appear adequate with patients no more likely to be on primary preventative medication after they join AAA surveillance [ 9 ]. It has been demonstrated that patients undergoing major vascular surgery, such as AAA repair, have an increased risk of perioperative major adverse cardiovascular events (MACEs) [ 10 ]. The high risk of MACEs is due to a combination of the patient’s multiple medical co-morbidities and the operative stress response and subsequent raised catecholamine and cortisol levels [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most recent American College of Cardiology (ACC) and American Heart Association (AHA) guidelines support preoperative stress testing for patients perceived to be at risk of cardiac events with poor or unknown functional capacity, if the results of the test will change management. 2,3 It should be noted, however, that current guidelines remain broad in scope, and are potentially less specific to the comorbidity profiles of many patients most likely to benefit from testing before surgery. 3,4 Accordingly, stress testing remains widely used, and controversy persists surrounding its optimal role in perioperative care delivery.…”
mentioning
confidence: 99%
“…This undoubtedly reflects the integral role that stress testing currently plays in contemporary preoperative risk stratification paradigms. The most recent American College of Cardiology (ACC) and American Heart Association (AHA) guidelines support preoperative stress testing for patients perceived to be at risk of cardiac events with poor or unknown functional capacity, if the results of the test will change management 2,3 . It should be noted, however, that current guidelines remain broad in scope, and are potentially less specific to the comorbidity profiles of many patients most likely to benefit from testing before surgery 3,4 .…”
mentioning
confidence: 99%